TOURISM PROMOTIONAL ACTIVITIES OF WUZHISHAN IN HAINAN PROVINCE, CHINA - Zhang Lu Yu; Supot Rattanapun (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
After 30 years of reform and development, Wuzhishan has become a major tourist city in Hainan. This article focused on tourism promotion modes advocated by the government of tourism administration has become a basic mode in developing Wuzhishan's tourism market sales. This research used theoretical and practical analysis of the government's tourism promotion modes. The current situation and features of tourism promotion by the Wuzhishan government were explored. To improve Wuzhishan's image and competitiveness, the government uses advertising, TV, newspapers, magazines, outdoor media, leaflets, etc. The government's tourism promotion timetable. Furthermore, Wuzhishan city tourism promotion happens in annual, seasonal, and monthly time & order distribution. The government's tourism strategy and measures. Moreover, Wuzhishan is Hainan's core ecological zone, which is an advantage. Protecting the local environment is essential for high-quality and leap-frog development. Therefore, it should be the country's top priority and not be delegated. In addition, the protection of scenic spots' original looks, the establishment of a long-term Gross Domestic Product (GDP) management mechanism, accelerated formulation and implementation of a tourism promotion plan, strengthening tourism promotion coordination, expanding government tourism promotion channels, and improved government tourism promotion.